(untitled) (مجلة المنصور, 2022)
Golay sequences have some properties make it distinctive in the applications and results. However, for this distinction must select the code sequences carefully and accurately. In this paper, an FPGA based, design and implementation for made autocorrelation of pair Golay complementary code sequences after extract all possible formations of 8bit code (192 8-bit pair code), and separate the unduplicated codes(12 at a time) and many (too many) 12 blocks 8-bit combinations with 16 main-to-sidelobe power ratio. There are another propose circuit attached to Tx and Rx which indicated by S1, S2 and S3 for increase the accuracy. Therefore, the Search can be regarded as pioneers of the research application of this technique on the subject and got good results. The Implementation was made by Xilinx-spartan-3A XC3S700AFPGA, with 50 MHz internal clock.